Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 621113 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Cyanobacteria" ] } The dataset includes 621113 records from 1277 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0179401-200613084148143/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences